Contextualizing the Artistic Repertoire in Museums: The Role of Nonartistic Factors. Issue 1 (1st July 2022) - Aldes, Liora; Katz-Gerro, Tally
Abstract: To remain financially sustainable while promoting cultural activity and operating within artistic, symbolic, and cultural norms, museums must consider a multitude of commercial and organizational elements. This article examines the impact of economic, organizational, and structural characteristics of art museums on the repertoire of art they exhibit. Using a mixed-methods approach, we draw on data pertaining to 11 art museums in Israel that are supported by the Ministry of Culture, analyzing administrative data collected yearly from the museums from 2000 to 2014. Next, we analyze 20 interviews with museum directors, curators, and artists to further explore the findings that emerge from the analysis of administrative data. Findings indicate three factors that influence a museum's artistic repertoire: revenue structure, museum location (center or periphery), and the museum director's preferences. We discuss these factors and explain the significant role that nonartistic factors play in shaping cultural outcomes.